Relationships, grief, and religiosity: an analysis of the discursive ethos in white horse and would've could've should've by Taylor Swift - SANTOS, Ellen Sylmara Sousa dos (2024)
This study aims to define and analyze the discursive ethos present in some songs by the singer Taylor Swift. The central theme of this research is the construction of identities in discourse, exploring the messages and narratives. The proposed analysis aims to examine the utterances in order to comprehend the formation and development of the ethos present in the selected songs, highlighting how their artistic statements shape the public perception. The research adopts the theoretical perspective of Maingueneau (2005, 2006, 2008, and 2014) on Discourse Analysis, Enunciative Scene, Discursive Ethos, which explores how attitudes and communicative conduct reflect the viewpoints and positions of a specific public. White Horse and Would've, Could've, Should've from the albums Fearless and Midnights, respectively, are analyzed. The research reveals that, through poetic narrative, Swift shares possibly personal experiences, establishing a deep connection with her audience who identifies with the themes and adheres to the speeches presented. Throughout the analyses, two distinct ethos were identified: one related to grief and the other with nuances of religious themes.